(untitled) (Molecular Medicine Communications, 2023)
In areas where both P falciparum and P vivax are co-endemic, and a patient is diagnosed with P falciparum malaria, the standard practice is to treat the acute infection with an appropriate antimalarial, often an Artemisinin-based combination therapy (ACT). Primaquine is not typically used for treating the acute P falciparum infection. However, adding primaquine to ACT could help reduce their risk of subsequent P vivax parasitemia. Thriemer and colleagues performed a multicenter clinical trial across Bangladesh, Indonesia, and Ethiopia. The primary endpoint was the incidence risk of P vivax parasitemia on day 63. This trial was registered at ClinicalTrials.gov, NCT03916003. The trial recruited 500 patients and the results suggest that there were very few serious adverse effects while 143 mild adverse effects were also reported. The incidence risk of P vivax parasitemia at day 63 was 11·0% (95% CI 7·5–15·9) in the standard care arm (low dose primaquine) compared with 2·5% (1·0–5·9) in the intervention (high dose primaquine) arm (hazard ratio 0·20, 95% CI 0·08–0·51; p=0·0009). These results suggest that high-dose short-course primaquine can reduce P vivax parasitemia risk within 63 days by fivefold. Lancet. 2023 Dec 2;402(10417):2101-2110. doi: 10.1016/S0140-6736(23)01553-2.